Correlation between Very Low-Density Lipoprotein and Trygliseride with Glycated Hemoglobin Levels in Type 2 Diabetes Mellitus Patients - Sherly Karolina Simanjuntak; I Nyoman Wande; Ida Ayu Putri Wirawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Patients with Type 2 Diabetes Mellitus (T2DM) have an increased prevalence of dyslipidemia, which contributes to ahigher risk of dyslipidemia- related complications in T2DM such as cardiovascular disease and stroke. This study aimed todetermine the correlation between TG and VLDL-C towards HbA1c levels in a person with T2DM. A retrospective study of 74outpatients with T2DM at Sanglah General Hospital, Denpasar, who examined serum HbA1c and lipid profiles were tracedfor serum TG. From the obtained TG profile, a secondary calculation of VLDL was carried out using the Friedewald equation(TG/5). A correlation test was used to determine the relationship between TG and VLDL-C towards HbA1c levels. Serum TG(212.95±147.46 mg/dL) and VLDL (36.69±23.54 mg/dL) were found to be higher in the group with poor glycemic control(HbA1c > 7 mg/dL) compared to serum TG (111.00±39.56 mg/dL) and VLDL (21.05±6.13 mg/dL) in the group with goodglycemic control (HbA1c ≤ 7 mg/dL) (p < 0.05). A positive correlation between serum TG (r=0.512; p < 0.001) and VLDL(r=0.18; p <0.001) towards HbA1c levels in T2DM patient was found. Insulin resistance increases the production of VLDL andApoC-III in the liver and increased chylomicron absorption in the gastrointestinal tract, causing prolonged postprandiallipemia and disruption of VLDL and TG clearance, thereby resulting in increased TG and VLDL in circulation. There is asignificant positive correlation between serum TG and VLDL towards HbA1c levels in a patient with T2DM.